Faktor Predisposisi Yang Mempengaruhi Keberhasilan Pemberian Asi Eksklusif Berdasarkan Teori Maternal Role Attainment Ramona T Mercer - Dwi Rahayu; Yunarsih Yunarsih (coba, 2017)
According to the Indonesian Demographic Health Survey (SDKI) from 1997 to 2002, the number of exclusive breastfeeding infants aged six months decreased from 7.9% to 7.8%. Meanwhile, the results of SDKI 2007 showed decreased number of exclusively breastfeeding infants up to 7.2% and the number of infants under six months who fed formula improved from 16.7% in 2002 to 27.9% in 2007. The number of infants in Indonesia who get exclusive breastfeeding continues to decline as more and more babies under 6 months of formula-feeding. The purpose of this research was to determine the factors that affect the successfull of exclusive breastfeeding Based On Maternal Role Attainment Ramona T Mercer Theory. The type of this research is an analytic survey. The population in this study are mothers who have babies aged 0-6 months in the Village Pojok Kediri. Sampling technique by Purposive Sampling and obtained the number of samples are 30 Respondents. The instrument used in this study is a questionnaire. Data analysis using Chi-Square test with α = 0,05. From the results of this study it was found that factors related to exclusive breastfeeding practices were maternal education (p value: 0,037), information how to breastfeeding (p value: 0,031), and community support (p value: 0,010), while Factors not related to Exclusive Breastfeeding practices include age (p value: 0.293), occupation (p value: 0.297), information of exclusive breastfeeding (p value: 0,903), Family Support (p value: 0.479) and Health Workers’s Support (p value: 0.669) . To improve the success of exclusive breastfeeding, counseling should be started from antenatal visit of the Pregnant Woman that aims to provide information preparation for breastfeeding, and counseling will be continued during breastfeeding which aims to monitor Exclusive breastfeeding up to 6 months and increase the participation of parents in exclusive breastfeeding support groups.